2006
DOI: 10.1002/ajmg.a.31158
|View full text |Cite
|
Sign up to set email alerts
|

Dural ectasia in children with Marfan syndrome: A prospective, multicenter, patient‐control study

Abstract: Even during childhood pathologic changes inside the lumbosacral spine of patients with Marfan syndrome can be observed. Dural ectasia, which occurs at different levels of the lumbar spine, can be detected at levels L5 and S1 in up to 40% of patients with Marfan syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 20 publications
2
22
0
2
Order By: Relevance
“…To our knowledge, no studies have investigated correlations between dural ectasia and cardiovascular manifestations within a pediatric patient population. The high prevalence of lumbosacral dural ectasia in MFS patients has been known for years and is again confirmed by the present study that showed a pathologic DSR in 90.3 % of the children [24]. The present study revealed no linear dependence between the dural sac ratio at spine segments L5 and S1 and the absolute diameter of the aortic root at the sinuses of Valsalva in pediatric patients with confirmed MFS.…”
supporting
confidence: 87%
“…To our knowledge, no studies have investigated correlations between dural ectasia and cardiovascular manifestations within a pediatric patient population. The high prevalence of lumbosacral dural ectasia in MFS patients has been known for years and is again confirmed by the present study that showed a pathologic DSR in 90.3 % of the children [24]. The present study revealed no linear dependence between the dural sac ratio at spine segments L5 and S1 and the absolute diameter of the aortic root at the sinuses of Valsalva in pediatric patients with confirmed MFS.…”
supporting
confidence: 87%
“…The prevalence of lens subluxation or luxation in our study, 62%, is the average of what is reported, 43,4 whereas the prevalence of fulfilling the major criteria for the skeletal system was 38%; other reports show large variation. 23,24 The involvement of skin and integument is comparable with the highest prevalence published. 23,27,44 Spontaneous pneumothorax has been rare in our cohort, whereas blebs in the lungs were found more often.…”
Section: Ghent Evaluation Of 105 Norwegian Adults S Rand-hendriksen Esupporting
confidence: 58%
“…It is important to check for aortic dissection, which may be small and focal [35]. MRI of the lumbosacral spine may be used to identify dural ectasia [36].…”
Section: Marfan Syndromementioning
confidence: 99%